Per un’analisi critica dell’esperienza bellica nella civiltà occidentale (dalla guerra-duello al bando “cieco” della così detta aggressione) (Stato, Chiese e pluralismo confessionale, 2023)
For a critical analysis of the war experience in the Western civilisation (from war-duels to the “blind” ban on so called aggression) *ABSTRACT: In taking up the threads of a meditation recently begun in this Journal, the Author manages to update its profile within an increasingly decisive criticism of the Briand-Kellogg pact: unnatural resolution of the dialectic between national interests in a pure et simple of so-called aggression of one state by another. The criticism moves in particular from the nature, no less brutally political than the war itself, of the UN decision to ban the alleged aggressor, without any analysys whatsoeverof the underlying reasons that constituted the basis for it, in the presence of a shared judging body and impartiality, capable too of suggesting possible conciliatory measures also with regard to the damage already caused by the war. The essay concludes by deriving the need to overcome the noted backwordness of the UN Charter on this point, channeling it into the context of a culture of “mild law”, inclined to wards the gradual overcoming of the “sovereign state” model, in the context of the recent development of nonimperial federal forms of coexistence and non- violent collaboration between nations.SOMMARIO: 1. Una premessa - 2. Sull’uso della forza nella rivoluzione oceanica - 3. Tra legittimismo ottocentesco e rivolta delle nazioni - 4. Sulle note di anarchia dei rapporti internazionali fra le due guerre mondiali - 5. (segue). ... e sulla fondamentale questione dell’impotenza giudicante dell’ONU - 6. Conflitto e aggressione nell’anarchia succeduta alla Santa Alleanza - 7. (segue) ... contro l’autodichia esasperata delle potenze egemoni - 8. Itinerari alternativi (non bellici) alla decisione di guerra -9. (segue) ... in tema di costituzioni europee e di coercizione nei trattati “di pace” - 10. Verso orizzonti nuovi in materia di riformismo costituzionale?